Perpendicular Magnetization Switching Driven by Spin‐Orbit Torque for Artificial Synapses in Epitaxial Pt‐Based Multilayers. (13th October 2022) - Zhang, Qiqi; Zhao, Yunchi; He, Congli; Huo, Yuping; Cui, Baoshan; Zhu, Zengtai; Zhang, Guangyu; Yu, Guoqiang; He, Bin; Zhang, Yi; Lyu, Haochang; Guo, Yaqin; et al.
Abstract: Perpendicular magnetization switching driven by spin‐orbit torque (SOT) exhibits nonvolatility and adjustability, which has great potential applications in magnetic random‐access memory and neuromorphic computing. In this work, the SOT efficiency in the Pt (001)/NiFe (Py) and Pt (111)/Py bilayers is first investigated, where the single crystal Pt films and polycrystalline Py films are grown by molecular beam epitaxy and magnetron sputtering, respectively. The (001)‐oriented Pt sample shows a larger SOT efficiency than that of the (111)‐oriented one, which is mainly attributed to the facet‐dependent intrinsic spin Hall effect of the Pt layer related to the Berry curvature of the electrical band structure. Then, the epitaxial Pt (001)‐based perpendicularly magnetized multilayers are designed to study the perpendicular magnetization switching driven by SOT. A continuous and stable reversal is successfully achieved, providing a conceivable candidate for reliable and variable imitation of the artificial synapses. The magneto–optical Kerr effect imaging proves that the sustainable change of magnetization state originates from the multiple site domain nucleation and growth in the ferromagnetic layer. This work provides an efficient method to enhance the SOT efficiency, as well as employs the epitaxial thin films in artificial synaptic devices for neuromorphic computing. Abstract : The stable multi‐level magnetization switching driven by spin‐orbit torque (SOT) has been successfully achieved in epitaxial Pt multilayers for mimicking the synaptic behaviors. And the results also reveal that the SOT efficiency in (001)‐oriented Pt layer is larger than that of (111)‐oriented one dominated by facet‐dependence of the intrinsic spin Hall effect.